2019
DOI: 10.1016/j.robot.2019.04.007
|View full text |Cite
|
Sign up to set email alerts
|

An ant-inspired celestial compass applied to autonomous outdoor robot navigation

Abstract: Desert ants use the polarization of skylight and a combination of stride and ventral optic flow integration processes to track the nest and food positions when travelling, achieving outstanding performances. Navigation sensors such as global positioning systems and inertial measurement units still have disadvantages such as their low resolution and drift. Taking our inspiration from ants, we developed a 2-pixel celestial compass which computes the heading angle of a mobile robot in the ultraviolet range. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 72 publications
0
37
0
Order By: Relevance
“…This method has been previously investigated and resulted in outstanding performances with a strong resilience toward both the meteorological and environmental conditions [26], [28]. The results also suggested that applying a median filter would have an interesting impact on the final heading estimation.…”
Section: A the Celestial-based Heading Estimationmentioning
confidence: 92%
See 4 more Smart Citations
“…This method has been previously investigated and resulted in outstanding performances with a strong resilience toward both the meteorological and environmental conditions [26], [28]. The results also suggested that applying a median filter would have an interesting impact on the final heading estimation.…”
Section: A the Celestial-based Heading Estimationmentioning
confidence: 92%
“…We developed an ant-inspired sky compass [25], [26] ( Fig. 1B-D) that analyses the polarization pattern of the skylight to extract the AoP around the zenith, corresponding to the heading of the vehicle with respect to the sun.…”
Section: A the Celestial-based Heading Estimationmentioning
confidence: 99%
See 3 more Smart Citations